Supplementation Moringa Leaves Powder (Moringa oleifera) in Ration on Performace of Super Village Chicken - Wasir Ibrahim; H Norida (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The aims of this study was to determine the Supplementation Moringa Leaves Powder (Moringa oleifera) in Ration on Performace of Super Village Chicken. Used 96 DOC super village chicken. The experiment was designed into completely randomized design with 6 treatments and 4 replicates. Treatments consisted of (P0) Moringa leaves powder 0% in Ration , (P1) Moringa leaves powder 2% in Ration, (P2) Moringa leaves powder 4% in Ration, (P3) Moringa leaves powder 6% in Ration, (P4) Moringa leaves powder 8% in Ration, (P5) Moringa leaves powder 10% in Ration. The parameters were feed consumption, average daily gain, feed conversion and mortality.. The data were analyzed by statistical product and service solution (SPSS 16.0) and significant effect among treatments were tested by Duncan’s multiple range test. the result showed that the Supplementation Moringa Leaves Powder were significant (P<0.05) in feed consumption and average daily gain. the conclusion of this experiment was that Supplementation Moringa Leaves Powder (Moringa oleifera) in Ration to 10% not influenced performance and mortality of Super Village Chicken.Keywords: Moringa Leaves Powder (Moringa oleifera). Super Village Chicken, Performance